Regulation of Tubulin Gene Expression: From Isotype Identity to Functional Specialization - Gasic, Ivana (Frontiers in Cell and Developmental Biology, 2022)
Genomes of higher eukaryotes encode a large tubulin gene superfamily consisting of at least 6 α and 6 β-tubulin isotypes. While some α and β-tubulin isotypes are ubiquitously expressed, others are cell-type specific. The subset of α and β-tubulins that is expressed in a given cell type is defined transcriptionally. But the precise mechanisms of how cells chose which α and β isotypes to express and at what level remain poorly understood. Differential expression of tubulin isotypes is particularly prominent during development and in specialized cells, suggesting that some isotypes are better suited for certain cell type-specific functions. Recent studies begin to rationalize this phenomenon, uncovering important differences in tubulin isotype behavior and their impact on the biomechanical properties of the microtubule cytoskeleton. I summarize our understanding of the regulation of tubulin isotype expression, focusing on the role of these complex regulatory pathways in building a customized microtubule network best suited for cellular needs.